Sikap Masyarakat dalam Pengelolaan Mangrove di Kampung Teluk Sulaiman, Kabupaten Berau, Indonesia - Gunawan Wibisono; Mustofa Agung Sardjono; Rujehan; Ali Suhardiman (Sodality: Jurnal Sosiologi Pedesaan, 2023)
This research aims to determine the value of community attitudes in Teluk Sulaiman in mangrove management and the factors that influence attitudes. This is a descriptive research using questionnaire and observation as data collection methods. Attitude measurement uses cognitive, affective, and conative aspects. To assess attitudes a Likert scale with SPSS processing is used. The results of the study obtained that the attitudes of the people in this village were positive with a value of 4.15, where the cognitive aspect value was 4.13, affective aspect 4.35 and conative aspect 3.96. The factor that influences attitude values is income. Meanwhile, other factors, such as age, and number of family members do not have a significant effect. Length of stay factor has a sufficient relationship with attitude value. The attitude scores seen from the gender segment do not have a significant difference, although in general the attitude scores of men are higher than women. The attitude scores of immigrants and native residents do not have a significant difference, although in general the attitude scores of immigrants are higher than those of native residents.